Analisis Pengaruh Endapan Polutan Dengan Metode Equivalent Salt Deposit Density (ESDD) Terhadap Tegangan Korona Pada Isolator Pin Post Di Jaringan Distribusi 20 KV Pekanbaru - M Putra Nurjanah; Firdaus Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Insulator pin post installed in an open space very coated ranges deposition of pollutants from the surrounding environment. Deposition of these pollutants will reduce surface resistance of the insulator, causing corona voltage (Corona Discharge). Corona voltage causing emergence of leakage current in the order of a few milliamps so that the insulator does not work well. The measurement method trough levels of pollutants using the equivalent salt deposit density (ESDD) which measures the conductivity of the weight of sediment pollutants then synchronized with the weight of the salt in aqueous solution so that its conductivity is equal to the conductivity of the pollutant deposition. This study analyzes how much influence the pollutant deposition occurs when the corona so that it can provide information that isolator placement terms of level of pollutant deposition. The results obtained are greater the value ESDD or deposition of pollutants, the lowervoltage corona. ESDD Value 0.09778619 corona occurs below the working voltage of 20 kV. InESDD value between 0 to 0.01477054 largest difference occurs against voltage ac corona at a voltage of 23.24 and at a dc voltage of 32.82.Keywords: Insulator pin post, ESDD, corona voltage